Accounting Students’ Academic Fraud: Empirical Evidence from Indonesia - Lisa Savilia; Nujmatul Laily (Universitas Negeri Malang, 2020)
The high rates of academic fraud in many countries make this research important to be conducted. This research aimed at investigating the factors which influenced accounting students’ academic fraud as seen from fraud triangle theory and 220 accounting students were randomly sampled to be its samples. The data were collected using a questionnaire distributed either in person to the respondents or using a google form. The data were analyzed using multiple regression. The research results indicated that fraud triangle (pressure, opportunity, rationalization) and academic entitlement had a significant influence on accounting students’ academic fraud. This means lecturers could minimize academic fraud among their students by reducing pressure, opportunity and rationalization as well as academic entitlement